Pengembangan e-Modul Panel Surya dengan Solar Tracker Single Axis pada Mata Kuliah Energi Baru dan Terbarukan Universitas Sebelas Maret - Rohim, Ficky Febrian Nur; Wijayanto, Danar Susilo; Saputra, Taufik Wisnu (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2024)
The Mechanical Engineering Education Study Program FKIP Universitas Sebelas Maret, there is one of the new courses in the 2021 curriculum (independent curriculum, independent campus learning), namely New and Renewable Energy. The learning tools in the course are not yet fully available. Learning tools continue to progress with the times, and e-modules are one of them. In this research developed a new and renewable energy learning e-module with a focus on utilizing solar energy using solar panels. Solar panels used are static solar panels and solar panels with a single axis solar tracker. The purpose of this study is to develop learning e-modules and find out the feasibility to be used in New and Renewable Energy courses. This study uses the Research and Development research method, with a 4-D model research model (Four D model), namely Define, Design, Development, and Disseminate. The Define stage results that the New and Renewable Energy course requires supporting learning tools, in the form of e-modules, e-module users are students of Mechanical Engineering Education class of 2021, with theoretical and practical learning concepts. The Design stage selects the format, drafts, and makes the initial draft. The Development stage tested the design results to two material expert lecturers, and the validation test of two media expert lecturers, then tested to 11 students. In the Disseminate stage, the e-module is submitted to the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta. For the results of this development research, in the expert test this e-module material obtained a score of 90.52% with a very decent category, in the media expert test a score of 88.88% was obtained with a very decent category. The results of the trial to students obtained a score of 84% with a very decent category.